Diagnosis and Endoscopic Management of Barrett's Esophagus: an Italian Experts' Opinion based document. Issue 12 (December 2017) - Costamagna, Guido; Battaglia, Giorgio; Repici, Alessandro; Fiocca, Roberto; Rugge, Massimo; Spada, Cristiano; Villanacci, Vincenzo
Abstract: Background: Barrett's esophagus (BE) is recognized as a risk factor for esophageal adenocarcinoma. An expert panel was organized in Italy with the aim of drafting a series of statements on BE to guide diagnosis and management of patients with BE. Methods: The working Group Coordinators worked on a literature search to identify key topics regarding critical steps of the endoscopic approach to BE. Based on the search and their expert opinion, a list of most meaningful questions was prepared and emailed to all members who were asked to vote the questions. When the survey was completed a consensus meeting was organized. According to the survey results, Group Coordinators proposed a draft statement that was voted. By definition, the statement was formulated when there was an agreement of ≥50% among participants. Results: Twenty nine participants deliberated 18 questions. The agreement was reached for 16 questions for which a recommendation was formulated. Conclusion: The generated statements highlight the Italian contribution to the European Position Statement of the European Society of Gastrointestinal Endoscopy. The Italian statements preserve peculiarities when dealing with the endoscopic management of BE and wishes to be considered as a contribution for the care of BE patients even with a low risk of progression to esophageal neoplasia.